2023
DOI: 10.3390/biomedicines11041061
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Articular Hyaluronic Acid in Osteoarthritis and Tendinopathies: Molecular and Clinical Approaches

Abstract: Musculoskeletal diseases continue to rise on a global scale, causing significant socioeconomic impact and decreased quality of life. The most common disorders affecting musculoskeletal structures are osteoarthritis and tendinopathies, complicated orthopedic conditions responsible for major pain and debilitation. Intra-articular hyaluronic acid (HA) has been a safe, effective, and minimally invasive therapeutic tool for treating these diseases. Several studies from bedside to clinical practice reveal the multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 109 publications
0
8
0
Order By: Relevance
“…In the in vivo study, the protective effect of ectoine on cartilage was evaluated using the OARIS scoring system. Intra-articular HA is a safe, effective, and minimally invasive therapeutic tool for treating OA [ 37 ]; therefore, we used HA as a positive control. The results indicated that the cartilage structure, chondrocyte number, S-O staining, and tide line integrity were lower in the ectoine and HA groups than in the OA group.…”
Section: Discussionmentioning
confidence: 99%
“…In the in vivo study, the protective effect of ectoine on cartilage was evaluated using the OARIS scoring system. Intra-articular HA is a safe, effective, and minimally invasive therapeutic tool for treating OA [ 37 ]; therefore, we used HA as a positive control. The results indicated that the cartilage structure, chondrocyte number, S-O staining, and tide line integrity were lower in the ectoine and HA groups than in the OA group.…”
Section: Discussionmentioning
confidence: 99%
“…By definition, orthobiologics are organic or synthetic materials that promote enhanced healing of musculoskeletal disorders [9]. Many orthobiologic products have been discussed in the literature, including acellular solutions like hyaluronic acid (HA) and cellular alternatives such as platelet-rich plasma (PRP), injectable platelet-rich fibrin (i-PRF), bone marrow aspirate/bone marrow aspirate concentrate (BMA/BMAC) and adipose tissue derivatives [10][11][12][13][14]. These products can have autologous or allogeneic origins and are known to contain a rich secretome and a wide variety of cells with potent stimulatory effects [15].…”
Section: Gradementioning
confidence: 99%
“…The effects elicited by PRP include cell recruitment, proliferation, differentiation, neovascularization, cytokine secretion, and inflammatory modulation [30]. Similarly, HA attenuates inflammation, induces lubrication, improves biomechanics, cell proliferation, differentiation, and migration, and favors anabolic reactions [13]. Collectively, these responses contribute to pain relief and the regeneration of damaged musculoskeletal structures, including bone, tendon, and cartilage.…”
Section: Gradementioning
confidence: 99%
“…In addition, these advanced manufacturing techniques allowed the production of HA hydrogels with improved biocompatibility and degradability, thus favoring their successful implantation in vivo [33,34]. These HA-based devices were applied in various medical fields giving successful results: in orthopedics, by promoting tissue regeneration and reducing inflammation in osteochondral lesions, osteoarthritis, and tendinopathies [35][36][37]; in dentistry, by improving wound healing after oral and maxillofacial surgery as well as in periodontics, endodontics, and dental implants [38,39]; in dermatology, by treating skin damage and injury [40][41][42]; in neurology, by helping nervous system healing in neurological disorders or after stroke [43][44][45]; in cardiovascular medicine, by recovering injured myocardial tissue [46]; in ophthalmology, by stimulating cornea repair [47]. In recent years, nanotechnology has been integrated in tissue engineering: organic and inorganic nanomaterials (nanoparticles, nanotubes, nanocrystals, etc.)…”
Section: Introductionmentioning
confidence: 99%